Effects of bisoprolol combined with torasemide on cardiac electrophysiology in patients with acute myocardial infarction and heart failure - Jing, Li; Shi, Qiangwei; Zhao, Shihao (Frontiers in Physiology, 2025)
ObjectiveThis paper aims to assess the impact of bisoprolol combined with torasemide on cardiac electrophysiological parameters in acute myocardial infarction (AMI) patients complicated by heart failure (HF).MethodsA total of 140 AMI-HF patients were randomized to either the control group (bisoprolol alone for 3 months, n = 70) or an experimental group (bisoprolol for 3 months plus torasemide for 2 weeks, n = 70). The corrected QT (QTc) interval, QT dispersion, B-type natriuretic peptide (BNP) levels, left ventricular ejection fraction (LVEF), serum creatinine, serum potassium, New York Heart Association (NYHA) classification, Borg dyspnea score, lower-limb edema resolution, systolic/diastolic blood pressure (SBP/DBP), heart rate (HR), incidence of ventricular arrhythmia (VA) and atrial flutter/fibrillation (AFL/AF), and cardiovascular and all-cause mortality were evaluated.ResultsBoth groups demonstrated statistically significant reductions in QTc interval, QT dispersion, BNP, NYHA class, Borg score, SBP, DBP, HR, along with increased LVEF at 2 weeks and 3 months post-treatment versus baseline, with the experimental group showing moderate improvement at 2 weeks post-treatment in all parameters than the control group (P < 0.05). The experimental group had high serum potassium levels and a greater rate of lower-limb edema-resolution at 2 weeks post-treatment than the control group (P < 0.05). No significant differences were observed between groups in cardiovascular or all-cause mortality (P > 0.05).ConclusionBisoprolol combined with torasemide improves cardiac electrophysiological parameters, cardiac function, symptoms, and hemodynamics in AMI-HF patients as early as 2 weeks into treatment.